A giant adrenal lipoma presenting in a woman with chronic mild postprandial abdominal pain: a case report - Kapetanakis, Stylianos (BioMed Central, 2011)
INTRODUCTION: Adrenal lipomas are rare, small, benign, non-functioning tumors, which must be histopathologically differentiated from other tumors such as myelolipomas or liposarcomas. They are usually identified incidentally during autopsy, imaging, or laparotomy. Occasionally, they may present acutely due to complications such as abdominal pain from retroperitoneal bleeding, or systemic symptoms of infection. We report a giant adrenal lipoma (to the best of our knowledge, the second largest in the literature) clinically presenting with chronic mild postprandial pain. CASE PRESENTATION: A 54-year-old Caucasian woman presented several times over a period of 10 years to various emergency departments complaining of long-term mild postprandial abdominal pain. Although clinical examinations were unrevealing, an abdominal computed tomography scan performed at her most recent presentation led to the identification of a large lipoma of the left adrenal gland, which occupied most of the retroperitoneal space. Myelolipoma was ruled out due to the absence of megakaryocytes, immature leukocytes, or erythrocytes. Liposarcoma was ruled out due to the absence of lipoblasts. The size of the lipoma (16 × 14 × 7 cm) is, to the best of our knowledge, the second largest reported to date. After surgical resection, our patient was relieved of her symptoms and remains healthy six years postoperatively. CONCLUSION: Physicians should be aware that differential diagnosis of mild chronic abdominal pain in patients presenting in emergency rooms may include large adrenal lipomas. When initial diagnostic investigation is not revealing, out-patient specialist evaluation should be planned to enable appropriate further investigations.